Living well in later life: The influence of sense of coherence, and socio-demographic, lifestyle and health-related factors on older adults' satisfaction with life - von Humboldt, Sofia (2014)
This study aims at exploring a structural model of satisfaction with life’s (SWL) predictors in a cross-national sample of older adults. A quantitative approach was followed with a cross-sectional study design. A community-dwelling sample of 1,234 older adults from four different nationalities residing in Portugal, was assessed regarding SWL, sense of coherence (SOC) and socio-demographic, lifestyle and health-related characteristics. Sampling was performed in lifelong learning centres’ message boards and local community centres’ list-serves in the Lisbon metropolitan area and in the Algarve region. Structural equation modeling was used to investigate a structural model of the self-reported SWL, comprising SOC, socio-demographic characteristics (age, sex, education, marital and professional status, household, adult children, income, living setting and religion), as well as lifestyle and health-related characteristics (physical activity, recent disease and medication). Significant predictors are SOC (β=0.733; p<0.001), religion (β=0.725; p<0.001), income (β=0.551; p<0.001), adult children (β=0.546; p<0.001), education (β=−0.403; p<0.001), living setting (β=−0.292; p<0.001) and medication (β=−. 197; p<0.001). The variables accounted for 24.8 % of the variability of SWL. Moreover, differences between the four nationality groups (F(3, 671)=3.671, p=0.066) were not found concerning SWL. Sense of coherence is the strongest predictor of self-reported SWL. Other predictors are religion, income, adult children, education, living setting and medication. The four nationalities did not present significant differences, concerning SWL. This study points out the potential factors that influence older adults’ SWL, in particular SOC, religion and income, as promoters of aging well, within a salutogenic model of health for older populations.